A Suspected Case of Canine Subcorneal Pustular Dermatosis - TOI, NORIKO; YAMASAKI, HIROSHI; HARUNA, AKIHIRO; GORYO, MASANOBU; UMEMURA, TAKASHI (Journal of the Japan Veterinary Medical Association, 1988)
The subject was a one-year-old, male, mongrel dog suffering from an incurable dermatitis with pruritus, symmetrical alopecia and incrustation. After various treatments, clinical and clinicopathologica examinations for more than one year, he was euthanatized and submitted for pathological examination. Histopathologically, skin lesions were composed of subcorneal pustules with mild acantholysis and negative IgG depositions, suspected as subcorneal pustular dermatosis (SPD).